2004
DOI: 10.1023/b:bege.0000023644.87050.1a
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Isolation and Subsequent Adult Behavior of Drosophila paulistorum. VI. Quantitative Variation in Cuticular Hydrocarbons

Abstract: Our previous studies have demonstrated that long-term chemical contact with heterospecifics during development minimized unproductive heterospecific matings among the six Drosophila paulistorum semispecies. When socially isolated from conspecifics, discrimination significantly decreased so that more ultimately unproductive heterospecific matings occurred. Such results suggest that learning and social experiences play roles in mate recognition, using chemical information. In investigations into the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 50 publications
2
38
0
1
Order By: Relevance
“…were inconclusive owing to a variety of weaknesses including small sample sizes, different treatments conducted over days or months in a system notorious for huge time effects, pseudoreplication, and confounds created by testing only a non-random sample of the flies (e.g. Mayr & Dobzhansky 1945;O'Hare et al 1976;Pruzan 1976;Kim et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…were inconclusive owing to a variety of weaknesses including small sample sizes, different treatments conducted over days or months in a system notorious for huge time effects, pseudoreplication, and confounds created by testing only a non-random sample of the flies (e.g. Mayr & Dobzhansky 1945;O'Hare et al 1976;Pruzan 1976;Kim et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Following the procedure of Kim and Ehrman (1998), a 7-day-old male and female pair was introduced without anesthetization into a modified Elens and Wattiaux (1964) chamber in a no choice situation. The bottom of the observation chamber was coated with a thin layer of fly instant medium.…”
Section: Courtshipmentioning
confidence: 99%
“…Memory persistence through the complete metamorphosis remains an enigma in holometabolous insects (such as Drosophila), because a large part of the nervous system is reorganized during this process. Studies involving mixed Drosophila culture (of two strains, sub-species or species) showed that pre-imaginal exposure to homo-versus heterospecific (or homo-versus heterotypic) chemical cues affect adult sexual behaviour and mate discrimination [24,50,51]. However, the identity of these cues currently remains unknown and neither H3B2 nor phenol seems sufficient to induce food-choice conditioning in either Drosophila species.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules can influence a variety of adult behaviours; namely aggregation, courtship, mating and aggression [19][20][21][22]. Pre-imaginal exposure to specific food components mixed, or not, with pheromones can also affect subsequent adult behaviour in Drosophila mojavensis, Drosophila arizonae [23] and Drosophila paulistorum [24], but the identity of compounds involved remains unknown.…”
Section: Introductionmentioning
confidence: 99%